1994
DOI: 10.1084/jem.180.5.1649
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte-specific expression and autoantigenicity of transaldolase in multiple sclerosis.

Abstract: SummaryAlthough the etiology of multiple sclerosis (MS) is unknown, there is compelling evidence that its pathogenesis is mediated through the immune system. Molecular mimicry, i.e., crossreactivity between self-antigens and viral proteins, has been implicated in the initiation of autoimmunity and MS. Based on homology to human T cell lymphotropic virus type I (HTLV-I) a novel human retrotransposon was cloned and found to constitute an integral part of the coding sequence of the human transaldolase gene (TAL-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
2
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 53 publications
1
79
2
1
Order By: Relevance
“…Catalytic activity of wild-type rTAL-H (50 ng) was also inhibited in the presence of 300/lg/ml purified immunoglobulins from MS patients ALV and LAK, by 37% and 26%, respectively (not shown). These data demonstrated that autoantibodies from patients with MS recognized not only the immunoblotted full-length TAL-H protein and its N-terminal fragment [13] but functionally relevant C-terminal epitopes as well. The pathological significance of inhibition of transaldolase activity by autoantibodies is unknown at this time, but capture of TAL-H by immunoglobulins on the surface of B lymphocytes may play an important role in presenting TAL-H to T cells.…”
Section: Lysine 142 Mediates Catalytic Activity Of Tal-hmentioning
confidence: 78%
See 3 more Smart Citations
“…Catalytic activity of wild-type rTAL-H (50 ng) was also inhibited in the presence of 300/lg/ml purified immunoglobulins from MS patients ALV and LAK, by 37% and 26%, respectively (not shown). These data demonstrated that autoantibodies from patients with MS recognized not only the immunoblotted full-length TAL-H protein and its N-terminal fragment [13] but functionally relevant C-terminal epitopes as well. The pathological significance of inhibition of transaldolase activity by autoantibodies is unknown at this time, but capture of TAL-H by immunoglobulins on the surface of B lymphocytes may play an important role in presenting TAL-H to T cells.…”
Section: Lysine 142 Mediates Catalytic Activity Of Tal-hmentioning
confidence: 78%
“…In fact, activated B cells, by virtue of antigen capture on their surface immunoglobulins, are particularly efficient presenters of low abundance antigens [27]. Proliferation of T cells was stimulated by TAL-H in both patients (LAK, stimulation index, SI = 3.1 [13]; ALV, SI = 4.6, not shown). The identification of enzyme inhibitory autoantibodies capable of binding to native TAL-H may provide an example of how specific autoantibodies can influence autoimmune T cell responses in patients with MS.…”
Section: Lysine 142 Mediates Catalytic Activity Of Tal-hmentioning
confidence: 90%
See 2 more Smart Citations
“…17 T cell responses and antibodies are also directed against all the major myelin proteins in MS including myelin basic protein (MBP), proteolipid protein (PLP)], myelin oligodendroglial glycoprotein (MOG), myelin associated glycoprotein (MAG), and MOBP. 17,19 Other protein components in the myelin sheath such as transaldolase and CNPase are targets of the immune response in MS. 19,20 Lipids and carbohydrates of the myelin sheath are also targeted in MS. 21 The immune response to one region of myelin basic protein has been studied the most intensively. The peptide between residues 82 and 99 on myelin basic protein is a major target of both T and B cell responses to MBP.…”
Section: The Antigenic Targets Of T Cells and Antibodies In Msmentioning
confidence: 99%